Olhares sobre uma cidade refletida: memória e representações de Santos Lemos sobre Duque de Caxias (1950-1980). - Almeida, Tania Maria da Silva Amaro de (2009)
The research focuses on the works of Silbert dos Santos Lemos, who wrote about the city of Duque de Caxias, covering the period between 1950 and 1980. It centers the analysis in representations of the city, reflecting about the documental power of literary sources concerning the region of Baixada Fluminense and, mainly, Duque de Caxias, as producer of meanings for Local and Regional History, in which the routine of city is represented and given to see. It includes, in addition to the relationship between history and memory, a reflection on the historical testimony of this columnist-reporter, examining which memories of the time are present in his literary production, aiming at understanding the complexity of conceptions, sketched by the author who wrote about his own contemporaneity, being defined as contribution to the research line Historicity Representation, Memory and Discourse. It is based on interdisciplinary as a mediating principle, as it uses dialogues between Literature and History to turn literary texts as tension fields in which the material conditions of life and the values and sensibilities are made explicit, allowing access to subjectivities in an age historically situated.